PLXNC1: A Novel Potential Immune-Related Target for Stomach Adenocarcinoma - Ni, Zhizhan; Huang, Chenshen; Zhao, Hongmei; Zhou, Jinzhe; Hu, Muren; Chen, Qing; Ge, Bujun; Huang, Qi (Frontiers in Cell and Developmental Biology, 2021)
Background：Gastric cancer is associated with tumor microenvironment and chronic inflammation, but the underlying tumor-promoting mechanisms still remain unknown. Methods：The ATAC-seq was used to identify genes with chromatin accessibilities in promoter regions. The RNA-seq datasets were performed to identify differentially expressed genes (DEGs). Pearson correlation analysis with the mRNA expression of three families of tumor-related inflammation TFs was used to filter downstream DEGs. Cox univariate survival analysis was performed to identify the prognostic value. The ImmPort database and CIBERSORTx algorithm were used to investigate the regulatory relationship between hub DEGs and immune cells. Immunohistochemistry (IHC) and multidimensional database were performed to verification. Results：In this case, we require 2454 genes with chromatin accessibility in promoter regions by ATAC-seq. Based on the gene expression profiles (RNA-seq), we identified 365 genes with chromatin accessibility and differential expression. Combined with the Cox univariate survival analysis, we identified 32 survival-related DEGs with chromatin accessibility. According to ImmPort database, CXCL3, PLXNC1, and EDN2 were identified as immune- related genes in STAD. By applying the CIBERSORTx algorithm and Pearson correlation, PLXNC1 was the only gene correlated with various immune cells, significantly associated with M2 macrophages. Furthermore, gene set variation analysis (GSVA) suggests the “hallmark_interferon_gamma_response” pathway was most significantly correlated with PLXNC1. Immunohistochemistry results revealed that PLXNC1 protein level was significantly higher in STAD tissues than in normal tissues (p < 0.001) Conclusion：PLXNC1, regulated by IRF5, is an immune-related gene that was significantly associated with M2 macrophages and poor outcome in stomach adenocarcinoma.